Study of the Potential Traffic Congestion in Intersection of Three the Sunset Road, Kerobokan Road, Seminyak Road-Badung, Bali - Yasada, Gede; Sutapa, I Ketut (International Journal of Psychosocial Rehabilitation, 2020)
In this research, a method of traffic survey and analysis methods with regulations Indonesian Road Capacity Manual, from the calculation capacity values obtained on Monday morning at 2,422.681 (passenger car unit) pcu / hours, noon at 2,366.819 pcu / hour, an afternoon of 2,419.124 pcu / hour. Wednesday morning at 2,320.774 pcu / hour, noon at 2,490.786 pcu / hour and afternoon at 2,404.315 pcu / hour. Saturday morning at 2,535.207 pcu / hour, noon at 2,588.231 pcu / hour and afternoon at 2,463.082 pcu / hour. From the calculation of the degree of saturation (DS) and the intersection can determine the level of service. unknown degree of saturation on Monday morning at 1.114, noon at 1.220, afternoon at 1.230, on Wednesday morning at 1.173, noon at 1.200, afternoon at 1.230, on Saturday morning at 0.98, noon at 1,101, afternoon at 1,195. Delay junction (Delay) on Monday the morning obtained at 24.612 sec / pcu, noon at 41.672 sec / pcu, afternoon at 45.256 sec / pcu service levels average D and E, on Wednesday morning by 34.37 sec / pcu, noon at 39.98 sec /pcu, afternoon at 49.256 sec / pcu average service levels D and E, on Saturday morning at 18.15 sec / pcu, noon at 25.39 sec / pcu, afternoon at 38.79 sec / pcu, Services Tertiary average C and D.